2017
DOI: 10.1055/s-0037-1601868
|View full text |Cite
|
Sign up to set email alerts
|

Novel STAC3 Mutations in the First Non-Amerindian Patient with Native American Myopathy

Abstract: Native American myopathy (NAM) is an autosomal recessive congenital myopathy, up till now exclusively described in Lumbee Indians who harbor one single homozygous mutation (c.1046G>C, pW284S) in the gene, encoding a protein important for proper excitation-contraction coupling in muscle. Here, we report the first non-Amerindian patient of Turkish ancestry, being compound heterozygous for the mutations c.862A>T (p.K288*) and c.432+4A>T (aberrant splicing with skipping of exon 4). Symptoms in NAM include congenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…Likewise, stac3 was recently identified as a component of the EC coupling machinery in association with debilitating congenital human myopathies (Stamm et al, 2008; Horstick et al, 2013; Nelson et al, 2013; Grzybowski et al, 2017). This autosomal-recessive disease was identified in a culturally isolated population of Native Americans (Stamm et al, 2008) but has since been observed in Middle Eastern, African, and South American individuals (Grzybowski et al, 2017; Telegrafi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, stac3 was recently identified as a component of the EC coupling machinery in association with debilitating congenital human myopathies (Stamm et al, 2008; Horstick et al, 2013; Nelson et al, 2013; Grzybowski et al, 2017). This autosomal-recessive disease was identified in a culturally isolated population of Native Americans (Stamm et al, 2008) but has since been observed in Middle Eastern, African, and South American individuals (Grzybowski et al, 2017; Telegrafi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, stac3 was recently identified as a component of the EC coupling machinery in association with debilitating congenital human myopathies (Stamm et al, 2008; Horstick et al, 2013; Nelson et al, 2013; Grzybowski et al, 2017). This autosomal-recessive disease was identified in a culturally isolated population of Native Americans (Stamm et al, 2008) but has since been observed in Middle Eastern, African, and South American individuals (Grzybowski et al, 2017; Telegrafi et al, 2017). Patients present with symptoms of muscle weakness, including short stature, kyphoscoliosis, talipes deformities, and drooping facial features, and increased susceptibility to malignant hyperthermia (Stamm et al, 2008; Grzybowski et al, 2017; Telegrafi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One patient with severe presentation (PN5) was compound heterozygous for the recurrent NAM and a novel splice site variant. Similarly, three other reported previously patients with a more severe phenotype carried variants other than the recurrent NAM variant (frameshift or splice site variants; Grzybowski et al, 2017;Telegrafi et al, 2017). However, it is worth noting that a degree of clinical variability is also observed among patients with homozygous NAM variant and among members of the same family, suggesting that factors other than the type of variants could contribute to the phenotypic variability.…”
Section: Discussionmentioning
confidence: 66%
“…Recently, recessive variants in STAC3 have been reported in patients with features overlapping Carey-Fineman-Ziter and Moebius syndrome (Grzybowski et al, 2017;Telegrafi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…NAM causes a range of debilitating symptoms including muscle weakness, delayed motor development, and malignant hyperthermia susceptibility, which in an estimated one third of the patients lead to death before the age of eighteen. Meanwhile, the STAC3 W284S variant has been found in myopathy patients with non-Native American ethnicity [ 33 , 90 ] and novel STAC3 variants were identified in patients presenting congenital myopathy symptoms and MHS; altogether constituting the category of STAC3-related congenital myopathies [ 108 ].…”
Section: Normokalemic Periodic Paralysis (Normopp)mentioning
confidence: 99%